Effect of breeds on haematological parameters and some serum biochemical profiles of goat exposed to heat stress - Tella, Adetunmbi; Ekeocha, Anthony; Adebayo, Francis Bosede; Oluwadele, Joshua; Aro, Samuel Olanrewaju (Talenta Publisher, 2025)
This study examined the effect of breed on serum biochemical profiles and haematological markers in heat-stressed West African dwarf and Red Sokoto goats. The Temperature Humidity Index (THI) was computed using the recorded ambient temperature and relative humidity of the research. 95 goats in the Nigerian states of Osun, Oyo, and Kwara—50 Red Sokoto and 45 West African Dwarf goat breeds—had blood collected from them, all of whom appeared to be in good health. Haematological parameters (Packed Cell Volume (PCV%), haemoglobin (Hbxg/dl), red blood cell counts (RBC x /µl), white blood cell counts (WBC x /µl) and serum biochemistry, which includes total protein (TP x g/dl), albumin (ALxg/dl), globulin (GL x g/dl ), albumin and globulin ratio (AL/GL%), glucose (GLU x Mg/dl), sodium( x mmol/L), potassium ( x mmol/L) and calcium ( x mmol/L) concentrations in RS and WAD goat breeds were carried out. The results of the investigation showed variations in haematological and biochemical parameters between breeds.